Inheriting Inequity: A Comparative Legal Dissection of Gender Discrimination in Indonesian Inheritance Law - Wulandari , Wahyuni Retno; Ahmad, Nadzriah; Fitriliani, Yulia; Purwaningsih, Rini (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
As Indonesia adopts Islamic law, civil law, and customary law in its legal system, it is suspected that some serious issues emerge in its implementation. One of them is gender inequality issue in its inheritance law. While the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) has been ratified by the country, discriminatory practices persist as a result of patriarchal interpretations of the law and dominant patrilineal customs. This study aims to analyze gender inequality in inheritance distribution by examining how legal systems in Indonesia align with or diverge from the international human rights norms, particularly CEDAW. Using a normative legal method and comparative approach, this study looked into the legal structure, substance, and culture of inheritance legal systems in predominantly Muslim countries such as Egypt, Tunisia, Morocco, Pakistan, Thailand, Malaysia, Singapore, Brunei Darussalam, and Indonesia based on Lawrence Friedman’s legal system theory. The results showed that Indonesia’s civil law had a tendency to conform to the international gender equality norms. However, the Islamic and customary inheritance practices in the country were still strongly influenced by patriarchal values. In comparison, some of the other countries studied in this research demonstrated greater flexibility in aligning their Islamic inheritance laws with the gender justice principles. These findings underscored the urgent need for Indonesia to develop context-sensitive legal reform strategies that include progressive ijtihad, transformation of patriarchal customs, and synchronization of the national inheritance law with the international human rights standards.